All about lemons: Over 60 DIY lemon recipes for health and household - Riley, Vanessa frey50 (San Bernadino, CA Vanessa Riley, 2015)
The lemon is a versitile fruit that can be used for many things besides lemonade. Read this book to find the variety of uses in the household and for your health.
The particular book was published December 20, 2015.
Keywords: Lemons - uses of. -- Kitchen. -- Cleaning. -- Health. -- Odds and ends; How to